The Effect of Drying Techniques on the Antioxidant Capacity, Flavonoids and Phenolic Content of Fermented Local Cocoa Bean - Alau Rining, Hadassah; Majid, Hafiz (Journal of Advanced Research in Applied Mechanics, 2020)
The effect of drying techniques namely sun drying, freeze drying, and oven drying on the antioxidant capacity, total phenolic and flavonoid contents of 3 clones of fermented local cocoa bean (BR25, MCBC6, PA76) was determined. The highest cocoa bean extraction yield was found using freeze drying, followed by sun drying, and oven drying method. The highest total phenolic content was obtained from freeze drying of BR25 with value of 1380.86±4.21 mg GAE/g, and the lowest was found in oven drying of PA76 with total phenolic content of 672.95±1.35 mg GAE/g. For total flavonoid content, the highest value was found from freeze drying method of BR25 with value of 4536 ±10.37 mg QE/g and the lowest was in oven drying of PA76 with flavonoid content of 2639 ±7.07 mg QE/g. Lower IC50 value indicated a stronger antioxidant activity of extracts. Results obtained show the same trend where the lowest IC50 value was obtained in freeze dry followed by sun dry and oven dry method. The lowest IC50 value was found in for freeze drying techniques of PA76 with value of 4.70±0.37 mg/ml and the highest was found in oven drying of MCBC6 with IC50 value of 369.17±1.29 mg/ml. Freeze drying method was found to be the best method to preserve highest amount of total phenolic and flavonoid content.